APLIKASI PENGELOLAAN LAHAN KELAPA SAWIT (APLKS) BERBASIS INFORMATION SYSTEM INTERACTIVE MAP DI KEBUN TINJOWAN - Surya Ningsih; Dewi Mutiara; Rizqan Khalish; Muhammad Ridha Syafii Damanik (Tunas Geografi, 2018)
The need for an easy and fast information system is a demand that must be answered in the current management of oil palm plantations. Application Development of Palm Oil Land Management (APLKS) based on Information System Interactive Map is one way to answer these demands. This research was conducted at Palm Oil Plantation of Tinjowan, North Sumatera Province. The purpose of this research is to know the accuracy of mapping and application of Palm Land Management Application (APLKS) in Tinjowan Palm Oil Plantation. The method used in this research is descriptive qualitative. Data collection technics used are documentary studies, direct observation, and application development. The analysis result shows that the level of Overal Accuracy (overall accuracy) mapping is 94,64%. The results of application implementation measurement indicate that this application is very helpful for companies in palm oil land management especially in the ease and speed of information access location and condition of plantation.